Systematic review of the literature on the occurrence and characteristics of dyspnea in oncology patients. (January 2023) - Shin, Joosun; Kober, Kord; Wong, Melisa L.; Yates, Patsy; Miaskowski, Christine
Abstract: Background: Dyspnea is a common and distressing symptom for oncology patients.However, dyspnea is not well-characterized and often underestimated by clinicians. This systematic review summarizes the prevalence, intensity, distress, and impact of dyspnea in oncology patients and identifies research gaps. Methods: A search of all of the relevant databases was done from 2009 to May 2022. A qualitative synthesis of the extant literature was performed using established guidelines. Results: One hundred-seventeen studies met inclusion criteria. Weighted grand mean prevalence of dyspnea in patients with advanced cancer was 58.0%. Intensity of dyspnea was most common dimension evaluated, followed by the impact and distress. Depression and anxiety were the most common symptoms that co-occurred with dyspnea. Conclusion: Numerous methodologic challenges were evident across studies. Future studies need to use valid and reliable measures; evaluate the impact of dyspnea; and determine biomarkers for dyspnea. Graphical Abstract: ga1 Highlights: Over 50% of patients with advanced cancer experience dyspnea. Intensity of dyspnea was the most common dimension evaluated. Occurrence of cardiopulmonary comorbidities is a significant risk factor for dyspnea. Functional exercise capacity was the most common measure used to evaluate the impact of dyspnea. Depression and anxiety were the most common symptoms that co-occurred with dyspnea.